AI-Driven Automation in a Human-Centered Cyber World - Norris Smith (2019)
© 2018 IEEE. Progress in artificial intelligence (AI) is impressive, exciting, and inevitable. As we previously discussed, there is strong evidence that increased automation often leads to both more jobs and changes in jobs without destroying them. To account for this position, we examine the impact of AI on medical technology, employment, economics, and the social world with an emphasis on a human-centered cyber world. We survey the application of deep learning, a much celebrated AI technique, in the medical world by considering some of its illuminating successes in surgery, diagnosis, breast cancer screening, and autopsies. We also shed light on how AI can help physicians augment their surgical skills as well as assist humans in finding suitable health care services. Furthermore, we argue that despite the uninterrupted line of AI-driven successes, cooperative human-machine coexistence in the age of AI-driven automation is, nevertheless, a realistic view. We support our position with a discussion of the future of work in the light of human nature as it manifests itself in psychology and relevant economic and social theories.